2022
DOI: 10.3390/ijms23158689
|View full text |Cite
|
Sign up to set email alerts
|

The Complement System, Aging, and Aging-Related Diseases

Abstract: The complement system is a part of the immune system and consists of multiple complement components with biological functions such as defense against pathogens and immunomodulation. The complement system has three activation pathways: the classical pathway, the lectin pathway, and the alternative pathway. Increasing evidence indicates that the complement system plays a role in aging. Complement plays a role in inflammatory processes, metabolism, apoptosis, mitochondrial function, and Wnt signaling pathways. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 117 publications
0
22
0
Order By: Relevance
“…C3 protein plays a central role in the activation of the complement system. The complement is a part of the immune system and consists of multiple components with biological functions such as defense against pathogens and immunomodulation (Zheng et al, 2022). The complement system is an ancient defense mechanism present in invertebrates and vertebrate (Bavia et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…C3 protein plays a central role in the activation of the complement system. The complement is a part of the immune system and consists of multiple components with biological functions such as defense against pathogens and immunomodulation (Zheng et al, 2022). The complement system is an ancient defense mechanism present in invertebrates and vertebrate (Bavia et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In the developing brain, the complement is involved in synaptic pruning mediated by microglial cells ( 48 ). This physiological process of eliminating unwanted synapses has been shown to be aberrantly activated in aging brain and in neurodegenerative diseases as well as in progressive MS ( 49 52 ). In a mouse model of AD, it has been shown that C1q, the initiating protein of the classical complement, is increased and associated with synapses before overt plaque deposition ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found three components ( C6, C8A, C8B ) of the complement system’s Membrane Attack Complex (MAC) among the shared downregulated genes. Few studies have examined how the complement system changes with aging 51 . Our finding that multiple components of MAC are downregulated with aging suggests that this could be functionally linked with aging.…”
Section: Main Textmentioning
confidence: 99%